Pengaruh Penggunaan Media Audio Visual terhadap Prestasi Belajar Siswa pada Mata Pelajaran PAI di SDN Kragilan Purworejo - Bidayatul Maghfiroh; fathudin fathudin (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
This study discusses the effect of the use of audio-visual media on students' learning achievement in the subject of Islamic Religious Education. This is interesting to discuss because an educator is required to have various skills that support their duties in teaching. One of these skills is how an educator uses learning media. This research uses quantitative methods. Based on the data analysis that the researchers conducted, it was concluded that, there was a significant positive effect between the use of audio-visual media and the learning achievement of Islamic Religious Education of grade VI students at SD Negeri Kragilan Purworejo.